Investigating whether serum IGF-1 and IGFBP-3 levels reflect the height outcome in prepubertal children upon rhGH therapy: LG growth study database - Minsun Kim (Public Library of Science (PLoS), 2021)
Serum insulin-like growth factor-1 (IGF-I) and IGF binding protein-3 (IGFBP-3) levels can be used to monitor the safety of recombinant human growth hormone (rhGH) therapy. In this study, we evaluated the changes in serum IGF-I and IGFBP-3 levels during rhGH therapy as a marker of height outcome in prepubertal children. Totally, 705 prepubertal children with short stature were enrolled from the LG Growth Study Database. Data for three groups of subjects were obtained as follows: Idiopathic GH deficiency (IGHD; n = 486); idiopathic short stature (n = 66); small for gestational age (n = 153). Serum IGF-I and IGFBP-3 levels at the baseline and after the 1st and 2nd year of rhGH therapy, as well as the Δheight standard deviation score (SDS), were obtained. Δheight SDS after the 1st and 2nd year of rhGH therapy had notably increased compared to that at the baseline for all three groups. IGF-I and IGFBP-3 levels in all three groups were significantly increased compared to those at the baseline (p <0.001). Δheight SDS was positively correlated with ΔIGF-1 SDS after the 1st year of therapy, ΔIGFBP-3 SDS after the 2nd year of therapy in the IGHD group, and ΔIGF-I SDS and ΔIGFBP-3 SDS after the 2nd year of therapy (p < 0.05), regardless of whether the height at the baseline was a covariate. The increase in IGF-I and IGFBP-3 levels during rhGH therapy was related to the growth response in children with IGHD. Therefore, it may be valuable to measure the change in serum IGF-I and IGFBP-3 levels, especially the latter, during rhGH treatment to predict the growth response upon long-term treatment.